Do astronauts benefit from autonomy? Investigating perceived autonomy-supportive communication by Mission Support, crew motivation and collaboration during HI-SEAS 1. (April 2019) - Goemaere, Sophie; Brenning, Katrijn; Beyers, Wim; Vermeulen, Angelo C.J.; Binsted, Kim; Vansteenkiste, Maarten
Abstract: The topic of astronaut autonomy has received increasing attention in recent spaceflight literature. However, the question of whether astronauts benefit from autonomy in space, and how autonomy can be fostered by Mission Control deserves further examination. The objective of the present research was to study how the experiences of autonomy relate to crew motivation (i.e., internalization, lack of defiance) and collaboration (i.e., crew-ground cooperation and irritation) during HI-SEAS mission 1, and how crew autonomy relates to Mission Support's perceived communication style in interacting with the crew. The study sample comprised all six volunteers, three women and three men, between 33 and 43 years of age ( M = 39, SD = 4), who participated in the HI-SEAS 1 mission, which simulated a four-month-long stay on Mars. During the simulation, measures of Mission Support's perceived autonomy-supportive communication, crew members' autonomy, motivation and crew-ground interactions were taken on a weekly basis during eight weeks. Data were analyzed using multilevel analyses. Results indicated systematic week-to-week variation between constructs, such that greater experiences of autonomy during a given week related to more internalization and acceptance of instructions, less oppositional defiance, and a more fruitful collaboration with ground support that week. Additionally, weekly variations in crew autonomy were positively related to weekly variations in perceived autonomy-supportive communication by Mission Support. Implications for future studies and human spaceflight are discussed. Highlights: Autonomy and motivation are introduced from a Self-Determination Theory perspective. Week-to-week variation in crew functioning were measured during HI-SEAS 1. Crew autonomy was positively related to motivation and crew-ground collaboration. Autonomy-supportive communication from the ground predicted greater crew autonomy. Implications for space agencies and future human space exploration are discussed.